Exploring the connectivity of dorsolateral prefrontal cortex and the modulatory impact of transcranial magnetic stimulation in adolescents with depression: a focus on pain-related cognitive processing - Dan Qiao; Yiran Li; Xiaoyu Zhang; Yujiao Wen; Xuemin Zhang; Lu Ma; Gaizhi Li; Chunxia Yang; Zhifen Liu (BMC Psychiatry)
Abstract Background Abnormal cognitive response to pain is consistently associated with deleterious outcomes among adolescents with depression. Highly relevant to both pain and cognition, dorsolateral prefrontal cortex (DLPFC) is important to understanding pain cognition. Our study aimed to characterize the circuit of DLPFC and the efficacy of transcranial magnetic stimulation (TMS) over DLPFC on pain cognition in adolescents with depression. Methods Using neuroimaging data, we first compared functional connectivity (FC) of DLPFC between 60 adolescents with depression and 65 controls. The patients were then divided into add-on TMS group (N = 30) and Sertraline group (N = 30). Clinical outcome was determined using Pain Vigilance and Awareness Questionnaire (PVAQ) and Pain Catastrophizing Scale (PCS). Finally, we conducted regression analysis to assess the effect that FC of DLPFC contributes to in predicting clinical outcome. Results FC analysis showed that compared to controls, patients displayed hyperconnection of left DLPFC - left triangular part of inferior frontal gyrus (IFG), which was significantly correlated with higher PCS total-, magnification- and helplessness-scores. Patients also showed hyperconnection of right DLPFC - right supramarginal gyrus (SMG), which was correlated with lower PCS total- and rumination- scores. After intervention, the add-on TMS group displayed significantly decreased score on PVAQ, PCS total and rumination. FC of left DLPFC - bilateral triangular part of IFG, - right SMG, as well as right DLPFC - left putamen, could predict the improvement of pain vigilance and magnification. Conclusion Our results point to a key role of DLPFC acting as a connection linking cognitive control and pain processing in adolescents with depression. Trial registration The study is registered in https://www.chictr.org.cn/ with a registration number ChiCTR2000039503 (date: 10.30.2020).